Did Paul Expect to Survive until the Parousia? A Suggested Re-reading of 1 Cor. 15.51–52 - Gathercole, Simon (Journal for the study of the New Testament, 2025)
This article questions the conventional interpretation of 1 Corinthians 15.51–52, especially as evidence that Paul assumed an imminent parousia. There are two main problems with the conventional view. First, the majority view of 1 Cor. 15.51 relies on a counter-intuitive reading of the syntax. Second, on 15.52, the usual interpretation must assume that the reference to ‘change’ there has a different scope from the similar statement earlier in 15.51. The constructive argument takes vv. 51 and 52 in turn. First, the proposed reading of v. 51 adopts a more natural understanding of πάντες οὐ and reconsiders the meaning of ‘shall sleep’ (κοιμηθησόμεθα). This yields the following sense: ‘None of us shall continue to sleep, but we will all be changed in an instant, in the blinking of an eye, at the last trumpet.’ This alternative view is strengthened by evidence that Paul envisages this last trumpet as waking the dead: Paul refers to a state of sleep coming to an end in v. 51, not the falling asleep of some believers . Second, in v. 52, Paul is not distinguishing between the living and dead but rather is concluding his answer to the questions about resurrection posed in 15.35.